Sustaining international schools in a changing policy and market environment: Stakeholder perspectives from Shanghai, China - Peng, Yihong; Alias, Bity Salwana; Wan , Xinyu; Mansor, Azlin Norhaini (Journal of International Students, 2026)
This study examines the sustainability challenges facing international schools in Shanghai, China, within a rapidly evolving policy, demographic, and market context. Drawing on qualitative data from administrators, teachers, and parents, the study employs qualitative content analysis to explore stakeholder perspectives on the key factors influencing institutional sustainability. The findings reveal that challenges are multifaceted and interconnected, including financial pressures, regulatory uncertainty, difficulties in talent recruitment and retention, and complexities related to cultural integration within diverse school communities. Guided by sustainable leadership theory, the study proposes a context-sensitive framework that emphasizes leadership adaptability, integrated curriculum and learning environments, stakeholder collaboration, strategic resource management, and responsiveness to external market dynamics.